Patient preferences for attributes of injected or infused preventive migraine medications: Findings from a discrete choice experiment. Issue 4 (8th February 2023) - Schwedt, Todd J.; Martin, Ashley; Kymes, Steven; Talon, Brian; Lee, Xin Ying; Cady, Roger; Asher, Divya; Karnik‐Henry, Meghana; Mulvihill, Emily; Bates, Dawn; Beusterien, Kathleen
Abstract: Objective: To assess preferences among adults with migraine for differentiating attributes of injected or infused preventive treatment options and evaluate their importance in determining a treatment choice. Background: Adults with migraine and health‐care providers consider many factors when making treatment decisions. Injected or infused preventive migraine treatment options differ in several attributes, including mode of administration and dosing frequency, which may be preferentially selected or avoided by patients. Understanding a patient's preference is important for clinicians as they advise on various treatment options. Methods: A total of 604 US adults diagnosed with migraine participated in an online survey that captured information on demographics, migraine history, and treatment preferences. A discrete choice experiment (DCE) was used to evaluate participants' preferences for specific attributes of injected/infused preventive migraine therapies. The DCE data were utilized to estimate attribute importance (expressed as a percentage) and identify subgroups that had different distributions of preferences. Results: In the overall migraine population, mode of administration (28.8%), durability of effectiveness (27.0%), and speed of onset (25.5%) had the highest relative importance, whereas administration setting (9.9%) and dosing frequency (8.8%) had the lowest. Four distinct subgroups were identified: Group 1 ( n = 128) preferred self‐injection administration and durability of effectiveness; Group 2 ( n = 189) expressed aversion to cranial injections; Group 3 ( n = 158) prioritized rapid speed of onset; and Group 4 ( n = 129) favored health‐care provider administration and durability of effectiveness. Conclusions: Speed of onset, durability of effectiveness, and mode of administration are key moderators of treatment preference among US adults with migraine. Certain segments of the migraine population prioritize specific treatment attributes over others, with intravenous infusion not considered a barrier in three of four identified segments. Clinicians can best help their patients find the right medication if they understand which medication attributes are most and least important to them.